2013
DOI: 10.1002/zaac.201300080
|View full text |Cite
|
Sign up to set email alerts
|

Merrifield and Wang Resins Functionalized with Bidentate Amines: Useful Materials to Support Reducing Complexes and as Alkali Metal Sensors

Abstract: Eight chelating resins were synthesized in high yields by supporting 2‐aminomethylpyridine, 2,2′‐dipyridylamine, 1,2‐phenylenediamine and 1,2‐ethylenediamine on Merrifield and Wang resins, respectively. These resins were used both as support of reducing complexes and as alkali metal sensors. 16 stable and easy to prepare reducing complexes, derived from the chelating resins and LiBH4 and NaBH4, were prepared in good yields. These complexes showed chemoselectivity to reduce aldehydes in a low molar ratio and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This consideration is essential for creating a material with specific properties. Merrifield resin is the most commonly used solid support for synthesizing peptides and CR since it has good thermomechanical stability and allows for the recovery and reuse of the CR [21][22][23][24][25]. In this context, Pina-Luis et al (2009) reported the synthesis of some CRs derived from Merrifield resin and amino benzamides labeled with a fluorescent group that showed high sensitivity to magnesium (Mg 2+ ) [24].…”
Section: Introductionmentioning
confidence: 99%
“…This consideration is essential for creating a material with specific properties. Merrifield resin is the most commonly used solid support for synthesizing peptides and CR since it has good thermomechanical stability and allows for the recovery and reuse of the CR [21][22][23][24][25]. In this context, Pina-Luis et al (2009) reported the synthesis of some CRs derived from Merrifield resin and amino benzamides labeled with a fluorescent group that showed high sensitivity to magnesium (Mg 2+ ) [24].…”
Section: Introductionmentioning
confidence: 99%
“…One disadvantage of the homogeneous synthesis is the difficulty to isolate the obtained product, since it is necessary to use chromatographic columns, extractions with different solvents or using specialized equipment such as HPLC. Solid phase organic synthesis (SPOS) plays an important role in combinatorial chemistry for the synthesis of new drugs and the development of new materials with molecular recognition properties . Polystyrene (PS) chloromethyl resins, like Merrifield and Wang, are the most useful polymers since they work under a wide range of reaction conditions and provide advantages such as facile preparation, environmental stability, recyclability, low cost, and non‐solubility in many organic solvents including water.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene (PS) chloromethyl resins, like Merrifield and Wang, are the most useful polymers since they work under a wide range of reaction conditions and provide advantages such as facile preparation, environmental stability, recyclability, low cost, and non‐solubility in many organic solvents including water. This kind of resins are very important materials in SPOS because they have been used as solid support in the preparation of chelating and reducing resins, peptides, antibodies, heterogeneous catalysts, molecular sensors and molecular fixatives . These properties make it an attractive material for heterogeneous procedures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anchoring would result in improved analytical properties, such as continuous readouts, increased sensitivity, lower reagent consumption, and the possibility of using the sensor in solvents in which the free molecule may display low solubility. Resin bound fluorescent chemosensors for several analytes have been made by combinatorial methods (Aguilar-Martínez et al, 2013;Brown et al, 2008;Castillo and Rivero, 2004;Joshi et al, 2007;Joshi et al, 2014;Nath and Maitra, 2006;Rivero et al, 2004;Santacruz Ortega et al, 2009). A variety of fluorescent motifs have been employed on the design of those materials, including dansyl group (Joshi et al, 2014), anthracene (Brown et al, 2008;Castillo and Rivero, 2004), aminenaphthalene sulfonic acid (Santacruz Ortega et al, 2009) and pyrene (Nath and Maitra, 2006).…”
Section: Introductionmentioning
confidence: 99%